Establishment of an oral burn model in streptozotocin-induced diabetic rats - Su-Young Kim; Seong-Gon Kim; Dae-Won Kim; Ji-Hyeon Oh (Maxillofacial Plastic and Reconstructive Surgery)
Abstract Background Oral ulcers are painful mucosal lesions prone to infection and inflammation. To evaluate the effectiveness of treatments, a suitable experimental animal model with an appropriate healing period is required. The aim of this study was to develop an animal model for oral ulcer research by comparing oral burn wounds of different sizes and locations in diabetic rats. Methods Forty-four male Sprague–Dawley rats with induced diabetes were divided into six groups based on burn wound location and size: T5 (n = 10, tongue 5 mm), T3 (n = 10, tongue 3 mm), P5 (n = 10, palate 5 mm), P3 (n = 10, palate 3 mm), CT (n = 2, control tongue), and CP (n = 2, control palate). The burn wounds were induced by applying a heated device (100–120 °C) for 3 s. At 1- and 2-weeks post-surgery, macroscopic examination, histological staining, immunohistochemistry, and Western blot analysis were performed to compare the healing progress. Results Healing progressed more rapidly in the second week than in the first for all groups, with burns on the tongue (Groups T5 and T3) showing more advanced healing compared to burns on the palate (Groups P5 and P3). By the second week, Group T3 was almost completely healed, while Group T5 had some remaining wounds. In contrast, Groups P5 and P3 showed minimal healing. This faster healing on the tongue was further supported by significantly lower expression levels of TNF-α and IL-1β and a reduction in ulcer size, particularly on the tongue compared to the palate. Conclusion A 3 mm or 5 mm burn wound on the tongue of diabetic rats can serve as a useful animal model for evaluating new treatments for wound healing, particularly up to the first week. However, for studies extending to the second week, the 5 mm burn wound model on the tongue might be more advantageous.